The Development of AWL (Academic Word List) Pocket Book to Facilitate Vocabulary : English - albadri Albadri; Maisatur Rizkiyah (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2023)
Students who took foreign language courses such as English Education department in addition to being required to have a myriad of vocabulary in English, in practice they must have great word diction used at the college level. In addition, students prioritized assignments rather than improving their vocabulary skills . The same problem to students in the fourth semester of the English Education Department of Social Science and Humanities Faculty of Ibrahimy University. In reality, most of the students had some difficulties when understanding and classifying the kinds of academic word lists and differentiating between AWL and the daily life vocabulary they used to speak. Thus, students are given exercises in increasing vocabulary to improve their abilities. Researchers use development (R&D) methods in their applications. The Validation data is used by experts, lecturers, and student appraisals to know the eligibility level of the pocketbook. From the result of the questionnaires given. AWL pocketbook got a very competent level by detail such as 81.33% from content expert validator, 70.66% from media expert validator, 89.33% from lecturer response, and 90.35% from students testing. Those results showed that AWL pocketbook showed a significant increase so that it can be used in the learning process